(untitled) (Fiep Bulletin - online, 2015)
The increase of age is associated with complex changes in some factors as: increase of body weight, BMI and blood pressure; once that those are directly associated. The purpose of this study was to verify and compare the level of arterial systolic and diastolic pressure, percent body fat and BMI of male and female related to age. 307 subjects were evaluated, 146 males and 161 females, 15 to 60 years old, that were distributed among 5 age levels: (1) 15-19, (2) 20-29, (3) 30-39, (4) 40-49, (5) 50-59. The data were evaluated through the program STATISTICA 6.0; the comparisons across age levels were made using ANOVA and post-hoc of Tukey. Significant differences in the female group can be observed from 30 year-old age level on, which overreach the regular values of BMI and arterial pressure, being classified as overweight and pre-hypertensive; the values of female body fat overreach the mean values of the lower category, maintaining until 30 years old; when there is a peak of fat accumulation between 40 59 years old. Until 29 years old, the classification of the male BMI is considered normal, after this age level it presents values classified as overweight and hypertension, where the peak value is between 40 and 49 years old; the fat body values were also above the mean values at all age levels, showing a peak after 50 years old. These results permit to conclude that three factors (AP, IMC and %F), present relevant increases at the third age level from 30 to 39 years old, both to male and female; factors that predispose subjects to higher risks of metabolic diseases and cardiovascular changes.